INFORMED CHOICE AND FEMALE STERILIZATION IN SOUTH ASIA AND LATIN AMERICA. Issue 6 (18th January 2018) - Jadhav, Apoorva; Vala-Haynes, Emily
Summary: Globally, female sterilization is one of the most popular contraceptive methods despite concerns about quality of care for women who report being sterilized. In this study, informed choice among sterilized women was quantified using Demographic and Health Survey (DHS) data from 2000 to 2012 for countries in South Asia and Latin America. Three responses measured informed choice and knowledge about whether women were informed by a health worker or provider: that sterilization is permanent, the potential side-effects of sterilization and other methods of contraception. An ascending composite Method Information Index with scores ranging from 0 (women received no information) to 3 (women received information across all three indicators) was used. Using ordinal logistic regression analysis, the results indicated that women younger than 25 and older than 35 at the time of sterilization, and those at high parities, had lower odds of a high score on the index, while the opposite was true for women sterilized in the private sector in Latin America. Educated women in India had higher odds of a high score on the index, while the same was true for educated and wealthy women in Colombia. These findings indicate that not enough health care providers spend time informing women in South Asia and Latin America about different aspects of sterilization, and that there are specific groups of women that are more affected. There is an urgent need to improve quality of care within health systems providing sterilization for this very important and effective type of contraception.